2010
DOI: 10.1089/met.2009.0084
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Hyperuricemia in Middle-Aged, Urban Chinese Men

Abstract: Background: Hyperuricemia is associated with metabolic syndrome and has emerged as a marker for both type 2 diabetes and cardiovascular disease. We estimated the prevalence and lifestyle risk factors of hyperuricemia in middle-aged, urban Chinese men. Methods: The study included 3,978 urban Chinese men 40-74 years of age from a population-based cohort study, the Shanghai Men's Health Study, who were free of type 2 diabetes at baseline and had provided fasting blood samples. Uric acid concentrations were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 45 publications
4
29
1
3
Order By: Relevance
“…However, it has been reported that physical activity is inversely related to the prevalence of hyperuricemia [49]. As moderate intense physical activity may also be associated with lower uric acid concentrations in obese individuals [50], further studies are needed to clarify the relationship between physical activity and IC development in the young population.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that physical activity is inversely related to the prevalence of hyperuricemia [49]. As moderate intense physical activity may also be associated with lower uric acid concentrations in obese individuals [50], further studies are needed to clarify the relationship between physical activity and IC development in the young population.…”
Section: Discussionmentioning
confidence: 99%
“…We further separated the participants according [30][31][32] , where the intake of purine-rich marine products is dominant, contributing to hyperuricemia and possibly MetS. In contrast, many studies [32][33][34][35][36][37] have found that an elevated SUA level is associated not only with purine intake from seafood, meat and beer, but also the presence of endogenous metabolic disorders.…”
Section: Association Between the Sua Level And The Incidence Of Mets mentioning
confidence: 99%
“…Of note, only a few studies corrected for alcohol consumption and smoking and hardly any studies corrected for renal function or use of diuretics, which are associated with diabetes and serum uric acid levels [32,33]. Further, physical activity may also confound the association and adequate correction is limited by imperfect measurement [34].…”
Section: Main Findingsmentioning
confidence: 99%